How dirty is your QWERTY? The risk of healthcare pathogen transmission from computer keyboards. (June 2021) - Ledwoch, K.; Dancer, S.J.; Otter, J.A.; Kerr, K.; Roposte, D.; Maillard, J-Y.
Summary: Introduction: Healthcare environmental surfaces may be contaminated with micro-organisms that cause healthcare-associated infections (HCAIs). Special attention is paid to near-patient surfaces but sites outside the patient zone receive less attention. This paper presents data on keyboard contamination and the risk of pathogen transmission from keyboards. Methods: Keyboards from nursing stations in three hospitals and a dental practice were analysed for bacterial contamination. Surfaces were pre-treated to remove planktonic bacteria so that any remaining bacteria were presumed to be associated with biofilm. Bacterial transfer from keyboard keys was studied following wiping with sterile water or sodium hypochlorite. The presence of multi-drug-resistant organisms (MDROs) was sought using selective culture. Results: Moist swabbing did not detect bacteria from any keyboard samples. Use of enrichment broth, however, demonstrated MDROs from most samples. Gram-negative bacteria were recovered from almost half (45%) of the samples, with meticillin-resistant Staphylococcus aureus, vancomycin-resistant enterococcus and MDR Acinetobacter spp. recovered from 72%, 31% and 17% of samples, respectively. Isolates were transferred from 69% of samples after wiping with sterile water, and from 54% of samples after wiping with 1000 ppm sodium hypochlorite. Discussion: While moist swabbing failed to detect bacteria from keyboards, pathogens were recovered using enrichment culture. Use of water- or NaOCl-soaked wipes transferred bacteria from most samples tested. This study implies that hospital keyboards situated outside the patient zone commonly harbour dry surface biofilms (DSBs) that offer a potential reservoir for transferable pathogens. While the role of keyboards in transmission is uncertain, there is a need to pursue effective solutions for eliminating DSBs from keyboards.